URBAN ELEMENTS IN SHAPING SUSTAINABLE TOURISM AREA IDENTITY - Frits Ontang Poedjianto Siregar; Raymond Christmas Tarore; Esli Davis Takumansang (CV. TOTUS TUUS, 2026)
Sustainable tourism areas require spatial environments that protect ecological resources while producing a distinctive and memorable destination identity. This study analyzes the role of urban elements in shaping sustainable tourism area identity in an emerging coastal destination. A descriptive qualitative design was employed through field observation, semi-structured interviews, documentation, and literature review. The analysis focused on eight urban elements: land use, building form and massing, circulation and parking, open spaces, pedestrian pathways, supporting activities, signage, and environmental preservation. The findings show that the identity of the tourism area is shaped most strongly by coastal landscapes, natural open spaces, mangrove and coral reef ecosystems, and community-based activities. These elements strengthen sense of place, visual attractiveness, ecological value, and the authenticity of visitor experience. However, pedestrian facilities, wayfinding systems, parking management, and architectural design control remain insufficiently integrated with sustainability principles. The study formulates an Urban Elements-Based Tourism Area Identity Model, which positions spatial-physical, socio-cultural, visual-legibility, and ecological elements as interconnected determinants of sustainable destination identity. The model offers a conceptual framework for planners and policymakers seeking to balance tourism competitiveness, environmental conservation, and local identity.